Christian Burial Practice in the Early Middle Ages: Rethinking the Anglo-Saxon Funerary Sphere - Sayer, Duncan (History compass, 2013)
Anglo-Saxon burial practices are particularly interesting because there is considerable variation in the archaeological record. In the earlier period local communities used a single cemetery site and grave goods were a mode of expression that signalled difference. In the Christian period grave goods were not employed in the same way but this change may not have had religion as its central agent. Moreover, the context of display changed and diversity was found in the location of burial - Minster, churchyard, field cemetery or execution site, and amongst the social-signals that these contexts indicated were included rank and religious association as well as family and deviant status. Dissimilar numbers of children - up to 51% in churchyards compared to 25% in field cemeteries - show that cemeteries must have held a different meaning amongst different social groups, indeed England’s earliest Christian communities’ seem to have considered churchyards to be significant places for the burial of children, but not the rural family, a contrast which may also have extended to other social groups.